Indoor Fine Particle (PM2.5) Pollution and Occupant Perception of the Indoor Environment During Summer of the First Passivhaus Certified Dwelling in Latin America - Moreno-Rangel, Alejandro; Sharpe, Tim; Musau, Filbert; McGill, Gráinne (JNRD - Journal of Natural Resources and Development, 2018)
This study compares the only residential Passivhaus in Mexico (located in Mexico City) to a conventional building-practice home in terms of indoor environmental quality during summer, specifically indoor air quality (IAQ) and the occupants’ perceptions towards it. Temperature, relative humidity, carbon dioxide, and PM2.5 were monitored during May, June and July 2016 in the living room, bedroom and kitchen of each home. Simultaneous outdoor air measurements were collected from the local pollution monitoring network. Online surveys were used to obtain data on building-related illnesses; while occupant perception of IAQ and thermal comfort and occupant diaries helped to provide insights into occupant behavior. Results from this case study suggest that Passivhaus design strategies could help to protect building occupants from outdoor air pollution, based on the lower concentrations of PM2.5 that were found in the Passivhaus apartment compared to the external environment. This contrasted with the results of the control home where PM2.5 levels were higher than ambient levels. Whilst the results cannot be generalized, they do provide much needed evidence on the indoor environmental performance of a Passivhaus-certified dwelling in Latin America, highlighting areas for improvement and providing recommendations to help inform future developments adopting these principles in a subtropical highland climate.